Practices in taste maintenance. The case of Indian diaspora markets. (August 2019) - Gowricharn, Ruben
This article centres on taste as a crucial driver of consumer behaviour and addresses the issue of how ethnic tastes in hybridized diaspora communities are maintained. The most common answer to this question refers to glocalization, which is briefly described as the adoption (modification) of global elements in the local culture. The article argues that the glocalization of taste occurs through consumer practices, but the concept of practices has been found difficult to apply, as there is no unified definition of it. Accordingly, each time the question of 'taste for what?' may be asked. Taste for dresses is something quite different, for example, than the taste for food – and so are the related practices. The concept of taste is therefore specific, as are the operationalized consumer practices. Put differently, taste appears to be a fuzzy concept that must be specified in each case in order to disclose its concrete meaning. Consequently, the article specifies that taste is shaped, maintained and expressed in and through consumer practices that need to display cultural scripts and institutional regularities in the lived culture of the ethnic community. Furthermore, the ethnic lived culture is differentiated from the concepts of 'everyday ethnicity', 'cultural norm images' and 'invention of tradition', detailing the home culture, the community culture and the celebration of traditions, respectively, to highlight how script-driven institutional practices sustain diaspora-related taste. Acknowledging that the specific mode of glocalization varies across diaspora communities, this article elucidates the argument with a case study by Dutch Hindustanis. The article claims that despite being a case study, the maintenance of taste applies to all communities that constitute the Indian diaspora market.